The Miraculous in The Stories of Prophets - Bintaleb, Sherefah Ibrahim (Arab Journal for Sciences and Research Publishing, 2021)
This study aims to reveal the miraculous in the stories of prophets which is a large topic intertwined with similar terms such as the myth, strange and superstition. This study tried to stand at the most prominent manifestations of the wondrous of Al- Tha'labi in his book " Arais Al- Majalis", through which Al- Tha'labi drifted behind a lot of wonders and marvels that concerned scholars in the past and present. The study also found that the more Al- Tha'alabi goes deeper into the wondrous, the closer he got to the literature and entertainment which is one of the most important intentions of the authors in the books of the stories of the prophets.
Keywords: The Marvelous; Narrative; Ancient; Stories of the Prophets; Brides of the Councils